2002
DOI: 10.1006/viro.2002.1588
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Infection and Release of Rift Valley Fever Virus in Polarized Epithelial Cells

Abstract: Rift Valley Fever (RVF) virus is an arbovirus and is responsible for large outbreaks of disease predominantly in sub-Saharan Africa. However, several aspects of RVF virus transmission, such as high viremia, multiple vector species, and broad host range, result in a pathogen with high likelihood of geographic spread. RVF virus infection in humans and livestock is characterized by broad dissemination of RVF virus antigens throughout the body. We sought insight into the high pathogenicity and broad tropism of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Within the Bunyaviridae family itself, little is known about polarity of infection. What has been clarified so far indicates an inconsistency of preferred entry site with apical entry for Black Creek Canal virus (Hantavirus) (24) and bidirectional entry for both Rift Valley Fever virus (Phlebovirus) (19) and Andes virus (Hantavirus) (26). We have also found that CCHFV was primarily released from the basolateral compartment in the epithelial MDCK-1 cells.…”
Section: Discussionmentioning
confidence: 75%
“…Within the Bunyaviridae family itself, little is known about polarity of infection. What has been clarified so far indicates an inconsistency of preferred entry site with apical entry for Black Creek Canal virus (Hantavirus) (24) and bidirectional entry for both Rift Valley Fever virus (Phlebovirus) (19) and Andes virus (Hantavirus) (26). We have also found that CCHFV was primarily released from the basolateral compartment in the epithelial MDCK-1 cells.…”
Section: Discussionmentioning
confidence: 75%
“…Infection of polarized epithelial cells with viruses in the family Bunyaviridae, including ANDV, leads to the polarized release of virus particles. This release can be strictly apical, strictly basolateral, or a combination of both (Chen et al, 1991;Connolly-Andersen et al, 2007;Gerrard et al, 2002;Ravkov et al, 1997;Rowe and Pekosz, 2006) Since Rab8 and Rab11 play roles in polarized trafficking (Ang et al, 2003(Ang et al, , 2004Brock et al, 2003), it is possible that ANDV utilizes these pathways to egress in a polarized fashion from cells. By utilizing the recycling endosome during egress, hantaviruses could be sorted in both the apical and basolateral direction and ensure appropriate viral spread and tissue tropism within the host.…”
Section: Discussionmentioning
confidence: 99%
“…RVFV are known to bud from Golgi membranes and the budding site seems to be defined by a retention of the glycoproteins G N and G C at that particular site [43,44]. Since bunyaviruses do not have a matrix (M) protein to link the viral surface glycoprotein G N and G C with the RNPs, a direct interaction between the RNPs and envelope proteins is expected.…”
Section: Aetiological Agent and Classifica-tionmentioning
confidence: 97%